Navigating agency and professionalism in translation and interpreting: A community of practice of coordinators for international relations in Japan - Shane Forde; Patrick Cadwell; Ryoko Sasamoto (JoSTrans: The Journal of Specialised Translation)
In the digital age, communities of practice are commonly situated in online spaces. This paper addresses the role that one online platform plays among a group of largely non-professional translators and interpreters working for local government bodies in Japan as coordinators for international relations (commonly referred to as CIRs) on the Japan Exchange and Teaching (JET) programme. The paper sets out to establish whether interactions on the forum represent an expression of a community of practice. It also investigates whether forum members leverage their interactions online to learn together and solve problems surrounding translation and interpreting. Forum-mediated communications were observed using a netnographic approach, and thematic analysis was conducted to examine the data gathered. Findings from this study establish the online forum as an expression of a distributed community of practice. Members use the forum to discuss linguistic issues inherent in translation and interpreting and macro-level issues such as professional status and agency. We conclude that the forum provides a useful avenue for members to tackle a range of issues that permeate translation and interpreting and result from a vacuum of appropriate translation and interpreting training and support.